Perbandingan Filsafat Pendidikan Muhammadiyah dengan Filsafat Pendidikan Barat: Sebuah Kajian Komparatif - Muhammad As’ad Humam; Bagus Jamroji; Sigit Sugiarto; Imam Ghozali (Educational Research Center, 2026)
This study comparatively examines the Philosophy of Education of Muhammadiyah and the Philosophy of Western Education to map the ontological, epistemological, axiological foundations, and their implications for educational goals, curriculum, and praxis. The main focus of the study is to trace the meeting points and differences between the Muhammadiyah educational paradigm which is rooted in the principles of monotheism, tajdid (renewal), and the orientation of social charity, and the mainstream of Western educational philosophy that develops through the traditions of humanism, progressivism, pragmatism, and critical pedagogy. The research uses a qualitative method based on library research with a comparative analysis design. Data was obtained through the study of key documents and texts, including Muhammadiyah educational decisions and thoughts, as well as representative works of Western educational philosophy. Data were analyzed using content analysis techniques and thematic comparison frameworks to assess concept coherence, value orientation, and practical consequences. The results of the study show that both traditions emphasize the formation of empowered, rational, and progressive human beings; however, Muhammadiyah places the transcendental dimension and prophetic ethics as the center of educational orientation, while many Western schools tend to affirm human autonomy, the secularity of knowledge, and the relativity of values in a historical-sociological framework. These findings affirm the importance of an integrative-critical approach in formulating modern and valuable education, as well as offering a conceptual model to strengthen the relevance of Muhammadiyah education in the global context without losing its normative identity.